Grandparenting: Created by Evolution Revised by History: Still in Use Today - Bóné, Veronika (European Journal of Mental Health, 2018)
The ageing of Western societies and its consequences have been long focused on by extended research. Taking care of the elderly is a heavy burden for the healthcare system, the social care system and for the families, and according to statistics and projections, more and more elderly people must be supported by less and less active employees. Our study approaches the issue of ageing from another perspective: what kind of advantages are provided by the presence of the elderly for the society, what kind of positive effects do they exert through their grandparent role on the families and the society they live in. A simultaneous trend, along with ageing, is the increasing postponement in childbearing and the decreasing fertility. By analysing the former studies and works we investigate whether more and more people are experiencing grandparenthood because of their lengthening lifespan enabling them to provide help and support for the family rearing children, or grandparenthood sets in in the life of the elderly in an age when they are physically and mentally limited. In the history of humanity the development of grandparenting was an important step in the spreading of the species by increasing the chances of survival. And though the natural environment has changed significantly, we are convinced that grandparenting can provide an answer for the challenges of the present era.